Cenozoic Exhumation of the Qilian Shan in the Northeastern Tibetan Plateau: Evidence From Low‐Temperature Thermochronology. Issue 4 (8th April 2020) - Wang, Weitao; Zheng, Dewen; Li, Chaopeng; Wang, Ying; Zhang, Zhuqi; Pang, Jianzhang; Wang, Yang; Yu, Jingxing; Wang, Yizhou; Zheng, Wenjun; Zhang, Huiping; Zhang, Peizhen
Abstract: The growth of the Tibetan Plateau is related to the Cenozoic India‐Eurasia plate collision; however, its growth and evolution to its present margins remain matters of debate. The Qilian Shan, which is located along the northeastern margin of the Tibetan Plateau, plays a central role in understanding the outward growth of the plateau. In this paper, we present new low‐temperature thermochronologic data from the hanging wall of the Huangcheng‐Shuangta fault (HSF) and the Lenglongling west region in the eastern part of the Qilian Shan. Cooling ages and thermal history modeling show increased exhumation rates at ~15 Ma along the HSF and ~5 Ma in the Lenglongling west region. We suggest that the middle Miocene beginning of rapid exhumation reflects the expansion of the larger Qilian Shan driven by thrust fault systems. The fast Pliocene exhumation may have been related to left‐lateral motion on the Haiyuan fault during the late stage of orogenic development. Post‐Miocene episodes of rapid exhumation in the eastern Qilian Shan are similar to those in other regions on the northeastern margin of the Tibetan Plateau, suggesting that middle to late Miocene initiation or acceleration of crustal shortening occurred along this margin. Key Points: Cooling ages and thermal history modeling show increased exhumation of the eastern Qilian Shan at ~15 Ma and ~5 Ma The middle Miocene rapid exhumation indicates expansion of the Qilian Shan driven by thrust fault systems The fast Pliocene exhumation may have been related to left‐lateral motion on the Haiyuan fault during the late stage of orogenic development